A metacognição associada a aprendizagem significativa: estudo envolvendo o conteúdo de análise combinatória - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This study aimed to verify if a greater metacognitive development student, has more conditions to establish a significant learning of combinatory Analysis content. The theoretical framework was based on Flavell's study of Metacognition and David Ausubel's Significant Learning Theory. In the adopted methodology for the study construction, we use a qualitative and quantitative approach with explanatory bias, explaining qualitative data through quantitative data. The participants were second-year high school students from a public school in Ponta Grossa City and data were collected through four instruments: prediagnostic and post-diagnoses tests with combinatory analysis problems, a questionnaire called Metacognitive Consciousness Inventory (MCI) and also a researcher journal with observations collected in the classroom during the approaching period of the combinatory content analysis by the discipline teacher. Through the analysis of the data obtained from the MAI, it was verified that this group of students in specific, presented the metacognitive processes developed in parts or developed, highlighting the elements of the structure of conditional knowledge and debugging strategies as the most developed. While the attitudinal elements of planning and evaluation capacity were less developed and as a result of these elements, the present difficulty in accessing previous knowledge and the capacity for interpretation was observed, hampering the action of solving combinatorial problems. These difficulties were perceived in the observations recorded in the researcher's diary, as well as expressed in the test resolutions. It was observed the existence of indications that the students with the best performance in the post-diagnosis test, had an above-average metacognitive development, so that these students showed signs of obtaining a meaningful learning of the contents of Combinatorial Analysis, so that they can infer that there is influence of the student's metacognitive processes in the consolidation of knowledge through meaningful learning.
Keywords: Metacognição; Aprendizagem significativa; Análise Combinatória; Metacognition; Significant learning; Combinatorial analysis; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA